Comparison of mesophilic and thermophilic anaerobic hydrogen production by hot spring enrichment culture - Puhakka, Jaakko A.; Karadag, Dogan; Nissila, Marika E. (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Anaerobic hydrogen producing mesophilic and thermophilic cultures were enriched and studied from an intermediate temperature (45 degrees C) hot spring sample. H-2 production yields at 37 degrees C and 55 degrees C were highest at the initial pH of 6.5 and 7.5, respectively. Optimum glucose, iron and nickel concentrations were 9 g/l, 25 mg/l and 25 mg/l both at 37 degrees C and 55 degrees C, respectively. The highest H-2 yields at 37 degrees C and 55 degrees C were 1.8 and 1.0 mol H-2/mol glucose, respectively, with the optimal pH, glucose concentration and iron addition. Hydrogen production from glucose at 55 degrees C and 37 degrees C was associated with ethanol- and acetate butyrate type fermentations, respectively. Bacterial composition was analyzed by 165 rRNA gene-targeted denaturing gradient gel electrophoresis (DGGE). Clostridium species dominated at both temperatures and the microbial diversity decreased with increasing temperature. At 55 degrees C, Clostridium ramosum was the dominant organism. Copyright (C) 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogen; Temperature; Mesophilic; Thermophilic; PCR-DGGE; Clostridium; BIOHYDROGEN PRODUCTION; WASTE-WATER; FERMENTATION; STARCH; PH; Chemistry; Electrochemistry; Energy & Fuels